PEMANFAATAN POTENSI KOPI DAN TRANSFORMASI DIGITAL GUNA MEMBERDAYAKAN MASYARAKAT DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN DI DESA SAJANG - Ardiansyah, Ardiansyah; Batubara, David Peterson; Sartika, Dewi; Tiara, Leni; Adrian, Muhammad Kholilul; Novayanti, Ni Putu Ari; Maulida, Soliha; Uciawati, Uciawati; Nurcahya, Wahyu; Setiawan, Agustono (Jurnal Wicara, 2023)
Sajang Village, Sembalun District, East Lombok Regency is one of the villages located at the foot of Mount Rinjani that has a very good coffee commodity but is only marketed by word of mouth. Digital transformation is the key to raising the potential of coffee commodities as a central element in local economic development. Sajang Village needs to publicize its coffee potential so that the wider community can easily get information about the village. Based on this problem, the community service program in Sajang Village provides assistance in developing an information system to manage coffee marketing in the village, as well as training in digital marketing management using the information management system that has been developed. The methods used are improving coffee marketing methods with attractive packaging, marketing coffee with garden tours, creating digital marketing accounts, as well as entrepreneurship training and marketing with social media. The purpose of implementing this program is to improve Sajang coffee products with attractive packaging, improve marketing with garden tourism by combining natural beauty, the authentic coffee production process, and educational experience, is not only a tourist destination, but also as a learning, providing media to publicize all the potential of the village so that it can be easily accessed by local and foreign communities, as well as conducting entrepreneurship and marketing training with social media to help develop the skills and knowledge needed to market Sajang Village coffee products through social media platforms. The result of this activity is the packaging of Sajang coffee products that are uniquely designed, making it easier to remember and identify by consumers, increasing farmers' income and encouraging economic growth in the area around the plantation, production and quality of Sajang coffee can increase through the application of digital technology so as to encourage local economic growth, and train how to market coffee products, equipping trainees with in-depth skills and knowledge to be able to market Sajang coffee products through various social media platforms.